2020
DOI: 10.1186/s12959-020-00227-w
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic duplication of anticoagulants: a retrospective study of frequency and consequences in a tertiary referral hospital

Abstract: Background: Anticoagulants are commonly prescribed in medical practices and could be of significant harm in the case of medication errors. We conducted a retrospective observational study to determine the frequency and consequences of the therapeutic duplication of anticoagulants (TDA). As a secondary objective, we aimed to determine the characteristics of the population in which TDA occurs. Methods: We conducted a retrospective observational study among admitted patients who concomitantly received at least tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The MHRA safety alert on anticoagulation identified a “small number of patients” co-prescribed warfarin and a DOAC, but provided no further information on the scale of the problem. One Swiss hospital found 0.8% of its patients on anticoagulant therapy (121/15812) were co-prescribed two anticoagulants in a single year, 2017/2018 [18]. However, 88.7% of these cases involved co-prescription of DOACs and injectable low-weight molecular heparins, not included in our study.…”
Section: Discussionmentioning
confidence: 87%
“…The MHRA safety alert on anticoagulation identified a “small number of patients” co-prescribed warfarin and a DOAC, but provided no further information on the scale of the problem. One Swiss hospital found 0.8% of its patients on anticoagulant therapy (121/15812) were co-prescribed two anticoagulants in a single year, 2017/2018 [18]. However, 88.7% of these cases involved co-prescription of DOACs and injectable low-weight molecular heparins, not included in our study.…”
Section: Discussionmentioning
confidence: 87%
“…One Swiss hospital found 0.8% of its patients on anticoagulant therapy (121/15812) were coprescribed two anticoagulants in a single year. 16 However, 88.7% of these cases involved coprescription of DOACs and low-molecular weight heparins, not included in our study. As regards INR tests, the MHRA reports appears to have been triggered by a root cause analysis from a single centre in London, 17 reporting that between 1 March and 17 April 2020, 0.9% (30/3214) of INRs were high (>8.0) compared with 0.1% (6/4079) the previous year.…”
Section: Discussionmentioning
confidence: 90%
“…The consequences of therapeutic duplication of anticoagulants have been studied previously, where 7.4% of cases led to a hemoglobin-relevant bleed. 40 In addition, our study found 3.4% of patients with an HAC linked to an anticoagulant resulted in hospital death. This further emphasizes the high-risk nature of anticoagulants and the need for concerted interventions to ensure their judicious and effective use.…”
Section: Discussionmentioning
confidence: 58%